STRATEGI PENGENDALIAN PENCEMARAN DAERAH ALIRAN SUNGAI (DAS) SIAK DI KABUPATEN SIAK - YESI GUSRIANI; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Abstract: pollution control strategies Watershed (DAS) in Siak regency Siak. This study aims to determine the pollution control strategy Watershed Siak . This study used a qualitative descriptive approach in which data collection was done by using snowball sampling . The results showed pollution control strategies Watershed ( DAS ) Siak Siak not run at max . Due to the environmental pollution control activities undertaken Environment Agency ( BLH ) Siak still exist problems that are still high rates of both water environment pollution , air or land , the unavailability of adequate infrastructure in carrying the good service and excellent and strategies pollution control can be done by increasing the inventory and identification of sources of water pollution , improve waste management , establish pollution load capacity , improve knowledge and community participation in waste management , improved control of the disposal of waste water and improve water quality monitoring of the river .Keywords: Strategy, Control, Water Pollution